2016
DOI: 10.1111/1750-3841.13234
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanocomposites from Whey Protein Concentrate Activated with Lycopene

Abstract: The production and characterization of nanocomposites based on whey protein concentrate (WPC) and montmorilonite (MMT) incorporated with lycopene as a functional substance is presented and discussed as an alternative biomaterial for potential uses in foodstuff applications. A full factorial design with varying levels of MMT (0% and 2% in w/w) and lycopene (0%, 6%, and 12% in w/w) was used. Color, light transmission, film transparency, moisture, density, solubility, water vapor permeability, and antioxidant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, the WVP (1.88×10 •s•Pa). This might be due to the complex film matrix formed at the higher concentration of HE and the more complex route of water passage (19).…”
Section: Physical Properties Of Rgrp Films Incorporated With Hementioning
confidence: 99%
“…However, the WVP (1.88×10 •s•Pa). This might be due to the complex film matrix formed at the higher concentration of HE and the more complex route of water passage (19).…”
Section: Physical Properties Of Rgrp Films Incorporated With Hementioning
confidence: 99%
“…Findings have lately suggested that novel WPI-based nanocomposites can be part of multilayer flexible packaging films, thus holding great potential to even replace well-established fossil-based packaging materials to support certain mechanical properties during storage [151,153,155,163]. Alternative biomaterials, have also been recently proposed for potential uses in foodstuff applications, via the production of nanocomposites from WPCs activated with lycopene and montmorillonite nanoparticles [164,168]. In another work, WPI nanocomposite films properties were reinforced with oat husk nanocellulose [154].…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%
“…WPC was evaluated, along with several selected biopolymers, as a potential vehicle to investigate L. rhamnosus GG survivability [165]. To date, only a few reports exist about probiotic activity in edible films and coatings from whey [164]. The possibility of implementing whey protein formations as a carrier matrix for viable probiotics could potentially result in better survival rates during storage and consumption, thereby promoting novel food applications.…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%
“…However, to gain insights on the potential application of these films for food packaging purposes, it is important to characterize these materials in terms of their barrier, mechanical, morphological and functional properties. In a previous study, we reported the stability, water vapor permeation, antioxidant activity and color characterization of whey WPC/MMT films with lycopene, showing the feasibility of processing such formulations for foodstuff uses. The aim of the present study is to perform a structural, mechanical and thermal characterization of these films that will provide useful data in order to help future definitions of applications.…”
Section: Introductionmentioning
confidence: 96%